Repetitive DNAs and shrink genomes: A chromosomal analysis in nine Columbidae species (Aves, Columbiformes) - Rafael Kretschmer; Thays Duarte de Oliveira; Ivanete de Oliveira Furo; Fabio Augusto Oliveira Silva; Ricardo José Gunski; Analía del Valle Garnero; Marcelo de Bello Cioffi; Edivaldo Herculano Corrêa de Oliveira; Thales Renato Ochotorena de Freitas (Genetics and Molecular Biology, 2018)
Abstract An extensive karyotype variation is found among species belonging to the Columbidae family of birds (Columbiformes), both in diploid number and chromosomal morphology. Although clusters of repetitive DNA sequences play an important role in chromosomal instability, and therefore in chromosomal rearrangements, little is known about their distribution and amount in avian genomes. The aim of this study was to analyze the distribution of 11 distinct microsatellite sequences, as well as clusters of 18S rDNA, in nine different Columbidae species, correlating their distribution with the occurrence of chromosomal rearrangements. We found 2n values ranging from 76 to 86 and nine out of 11 microsatellite sequences showed distinct hybridization signals among the analyzed species. The accumulation of microsatellite repeats was found preferentially in the centromeric region of macro and microchromosomes, and in the W chromosome. Additionally, pair 2 showed the accumulation of several microsatellites in different combinations and locations in the distinct species, suggesting the occurrence of intrachromosomal rearrangements, as well as a possible fission of this pair in Geotrygon species. Therefore, although birds have a smaller amount of repetitive sequences when compared to other Tetrapoda, these seem to play an important role in the karyotype evolution of these species.